Effects of new-to-market e-store features on first time browsers. Issue 90 (June 2016) - McKechnie, Sally; Nath, Prithwiraj
Abstract: Understanding the effects of website design features on website usage is complicated when buyers differ in their willingness to process information to make decisions. However, it becomes more difficult for a new-to-market e-store with no established familiarity. While extant literature suggests the use of interactivity and personalization features offered by e-stores to reduce consumers' risk perceptions and improve trustworthiness of such stores, there is little guidance on the level of feature provision required to enhance consumer satisfaction in making product selections from a new and unfamiliar e-store. The authors explore this issue in an online experiment with 273 subjects browsing 4 websites offering identical products but with variable levels of interactivity and personalization features. Findings reveal a positive association between the level of feature provision and browser decision-making outcomes. However, interactivity features are more effective for maximizers, whereas personalization ones are more effective for satisficers. Highlights: We examine the case of first time visitors encountering a new e-store. It shows how website features of a new e-store shape their browsing outcomes. We test the impact of task-facilitative tools for utilitarian browsing purposes. Users respond differently to a fixed choice set when we change levels of the tools. Usage of tools also varies according to their individual maximizing tendencies.